1993
DOI: 10.1016/s0022-5347(17)36099-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytophotometric DNA Quantification in Human Spermatogonia of Cryptorchid Testes

Abstract: The DNA content of spermatogonia was studied by cytophotometric quantification in the testes of cryptorchid children and adults, as well as in age-matched control males. In most cases, the average DNA content of spermatogonia was significantly increased in the cryptorchid testes of children with uni- or bilateral cryptorchidism, as well as in the contralateral scrotal testes of children with unilateral cryptorchidism. In the group of adult men the average DNA content of spermatogonia in the testes was even mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…The presence of roundish spermatogonia with electron-dense nuclei and large nucleoli has also been observed in cryptorchid testes of children (Ring et al, 1990;Codesal et al, 1993) and men (Codesal et al, 1993). It has been suggested that these cells have abnormal DNA content as a result of disturbances in DNA replication at above-scrotal temperatures (Ring et al, 1990;Codesal et al, 1993;Jannes et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The presence of roundish spermatogonia with electron-dense nuclei and large nucleoli has also been observed in cryptorchid testes of children (Ring et al, 1990;Codesal et al, 1993) and men (Codesal et al, 1993). It has been suggested that these cells have abnormal DNA content as a result of disturbances in DNA replication at above-scrotal temperatures (Ring et al, 1990;Codesal et al, 1993;Jannes et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Alterations in germ cell number are attributed to delayed and defective maturation of gonocytes into spermatogonia, and complete failure of transformation of spermatogonia into primary spermatocytes during the perinatal period (Cinti et al, 1993;Rozanski and Bloom, 1995;Zhou et al, 1996). Untransformed gonocytes and abnormal spermatogonia degenerate progressively throughout the prepubertal period (Codesal et al, 1993;Rozanski and Bloom, 1995), resulting in decreased numbers of spermatogonia in the abdominal testes of postpubertal males with unilateral and bilateral cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question is whether the maturational arrest of spermatogonia in testes with dysgenetic Sertoli cells should be explained either (i) on the basis of defective secretion of paracrine factors by the dysgenetic Sertoli cells or (ii) by a primary anomaly in most testicular cells. In cryptorchid testes, the occurrence of a primary anomaly has been supported by observation of abnormal DNA content in many testicular cells ( Codesal et al ., 1993 ), and it is possible that the same occurs in testes with dysgenetic Sertoli cells. In any case, the prognosis concerning fertility is poor in these testes.…”
Section: Discussionmentioning
confidence: 93%